1996
DOI: 10.1029/96jd00067
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the location of an arbitrarily oriented dipole under single‐point direction finding

Abstract: A lightning flash, cloud or cloud‐to‐ground, can be modeled by a time‐varying dipole, whose orientation may differ significantly from vertical, especially for cloud flashes. A direction finder measuring the vertical electric field and the horizontal components of the magnetic field over an infinitely conducting ground can estimate the location of the dipole with an accuracy that depends on the dipole orientation. A vertical dipole gives the best accuracy and a horizontal one the worst. With more than one direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
(2 reference statements)
0
16
0
Order By: Relevance
“…As shown by Panyukov [1996], a full identification of the dipole source is impossible if the measurement is performed at a single point at ground level. In this section we give an analysis of the minimal number of measurement points required for a unique identification, as well as an algorithm for a full identification of the dipole source.…”
Section: Measurements At Two Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Panyukov [1996], a full identification of the dipole source is impossible if the measurement is performed at a single point at ground level. In this section we give an analysis of the minimal number of measurement points required for a unique identification, as well as an algorithm for a full identification of the dipole source.…”
Section: Measurements At Two Pointsmentioning
confidence: 99%
“…It is assumed that the electromagnetic field is identically zero before t = 0, i.e., p(t) = 0 for t < 0. Many studies have been carried out during the past several decades on source identification problems related to the localization of thunderstorms or lightning [see, e.g., Horner, 1954; Ruhnke, 1962; Uman et al , 1980;Cooray, 1992;Panyukov, 1996). However, all these results concern estimates of partial information about the dipole source.…”
mentioning
confidence: 99%
“…The effective algorithm for the single-point distance determination to a pulsed EMR source was proposed and investigated in the papers [4,5], and pointed out to the emergence of irremovable uncertainty in the location of the EMR source by a one-point method caused by the difference in the orientation of the dipole from the vertical. The use of two or more observation points that do not belong to the same straight line makes it possible to determine the position parameters of the equivalent dipole [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the status of passive storm monitoring systems by the end of 2003 and the demonstration of the use of lightning-position detection systems for the passive radar of hazardous meteorological phenomena are presented in [1,2]. Modern methods for analyzing the field, allowing to determine the parameters of the source of EMP, characterizing its location and orientation are presented in the works [4,5,8] within the ISTC project #1822 was developed. As a result of the conducted field tests of this sample, during May-August 2004 more than 2.5 million atmospherics were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out during the past several decades on source identification problems relured to the localization of thunderstorms or lightning (see, e.g., Horner [1954], Ruhnke [1962], Urnan et al [1980], Cooray [1992], Panyukov [1996], and He et alo [2000]). Panyukov [1996] has shown that a full identi-In the present paper we use a global optimization technique (namely, a simulated annealing algorithm) to reconstruct simultaneously the location, orientation, and transient behavior of the dipole, using the electromagnetic fields measured at two or three points at the ground level. Optimization techniques can be grouped into two types, namely, global search methods and gradient search methods.…”
Section: Introductionmentioning
confidence: 99%